A New coat of leaves : a book about being accepting the way we look. (Asia : Time Life Asia, 1997)
The cedar tree is unhappy with the way it looks and makes several wishes to change its coat of leaves. By magic, each wish comes true, but the three finds that the new coat will not protect it against the natural dangers that surround it. In the end, the three realizes just why its own coat of leaves suits it best of all . . .
w/ casette tape
Keywords: Values; Aceeptance - Fiction